Myocardial infarction after intravitreal vascular endothelial growth factor inhibitors: a whole population study - Kemp, A.; Preen, D.; Morlet, Nigel; Clark, Antony; McAllister, I.; Briffa, T.; Sanfilippo, F.; Ng, Jonathon; McKnight, C.; Reynolds, W.; Gilles, M. (Lippincott, Wliiams & Wilkins, 2013)
Purpose: To determine the risk of thromboembolic and gastrointestinal bleeding events in the 12 months after injections of bevacizumab or ranibizumab compared with photodynamic therapy and a non-treated community sample.Methods: Hospital and death records were examined for 1,267 patients treated with vascular endothelial growth factor inhibitor and 399 patients treated with photodynamic therapy attending Western Australian eye clinics from 2002 to 2008, and 1,763 community controls, aged =50 years. Hospital records from 1995 to 2009 were analyzed for history of myocardial infarction (MI), stroke, and gastrointestinal bleeding before treatment. Records were searched for evidence of these events in the 12 months after treatment.Results: The 12-month MI rate was higher for vascular endothelial growth factor inhibitor patients than photodynamic therapy patients and the community group (1.9/100 vs. 0.8 and 0.7, respectively). No differences were observed between patients treated with bevacizumab and ranibizumab. The adjusted MI rate was 2.3 times greater than the community group (95% confidence interval, 1.2–4.5) and photodynamic therapy rate (95% confidence interval, 0.7–7.7). The 12-month MI risk did not increase with the number of injections administered (hazard ratio, 0.9; 95% confidence interval, 0.5–1.5). Stroke and gastrointestinal bleeding did not differ between any exposure groups.Conclusion: Although all the adverse events examined were rare, patients treated with vascular endothelial growth factor inhibitors were significantly more likely to experience fatal or nonfatal MI than the community group. This increased risk may be related to the underlying age-related macular degeneration or vascular endothelial growth factor inhibitor use itself.